2023
DOI: 10.12701/jyms.2022.00031
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the prescription of probiotics in patients with inflammatory bowel disease: a cross-sectional study

Abstract: Background: Commensal bacteria play an important role in the pathogenesis of inflammatory bowel disease (IBD) and probiotics have been used as treatment options. We aimed to explore the current use of probiotics and factors associated with their prescription in patients with IBD.Methods: This cross-sectional study was conducted on a single hospital-based cohort. Patients were eligible if they were ≥18 years old, visited the IBD clinic as an outpatient more than twice during the study period, and had a confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…Additionally, in combination with mesalazine, probiotics significantly improved symptoms of rectal bleeding and bowel movement frequency compared to mesalazine alone [23]. A study conducted in a murine model of ulcerative colitis (T-bet-/-Rag2-/-) showed that Bifidobacterium lactis reduces inflammation and colitis in the early stages of the disease and decreases the amount of Enterobacteriaceae, which appear to contribute to the development of intestinal disease [24].…”
Section: Ulcerative Colitismentioning
confidence: 99%
“…Additionally, in combination with mesalazine, probiotics significantly improved symptoms of rectal bleeding and bowel movement frequency compared to mesalazine alone [23]. A study conducted in a murine model of ulcerative colitis (T-bet-/-Rag2-/-) showed that Bifidobacterium lactis reduces inflammation and colitis in the early stages of the disease and decreases the amount of Enterobacteriaceae, which appear to contribute to the development of intestinal disease [24].…”
Section: Ulcerative Colitismentioning
confidence: 99%
“…Given the pathophysiological importance of the gut microbiome in UC, the hypothesis that altering the gut microbiota may be a viable way to treat UC is gaining attention ( Paramsothy et al, 2017 ). Based on a cross-sectional study, among patients with a high disease activity index (DAI), frequent defecation, severe abdominal pain, and a history of related surgery, the frequency of probiotics being prescribed increased, indicating that probiotics are now being recognized in the treatment of UC ( Kim and Cheon, 2022 ). Although the current evidence base supporting the use of probiotics in patients with UC is thin, probiotics are often widely used as adjunctive therapy and are often recommended by physicians, and they are generally considered to be safe ( Abraham and Quigley, 2017 ).…”
Section: Introductionmentioning
confidence: 99%